High-Frequency Ultrasonography As An Innovative Diagnostic Method in Dermatology - Rasińska, Aneta; Rzyczniok, Piotr; Rzyczniok, Anna; Weronika Rasińska; Jachimczak, Justyna; Grydź, Filip; Filipow, Joanna; Rebizak, Anna; Bala, Paulina; Rostkowska, Aneta; Kupisiak, Sebastian; Pasierb, Natalia; et al. (Quality in Sport, 2025)
Ultrasonography is now a standard, non-invasive imaging technique used in many areas of medical diagnostics. Currently it is also an important tool in the diagnosis of skin diseases. In clinical practice, High Frequency Ultrasonography (HFU) is used more and more often because it has proved to be a valuable diagnostic tool for assessing the condition of skin tissue. The physical conditions of HFU make it possible to estimate the parameters of the skin structure, such as thickness and echogenicity (a feature related to the center) of its layers in relation to the surrounding tissues. Therefore, HFU allows to obtain information concerning the condition of the examined area of the skin., the rate of lession development and the effectiveness of implemented theraphy. HFU is applied in the imaging of focal skin lesions, including melanoma, basal-cell carcinoma, inflammatory skin diseases, diseases associated with its thickening and in aesthetic medicine and cosmetology. The aim of this chapter is to familiarize the reader interested in dermatology and in particular diagnostics in this field, the possibilities associated with the use of HFU. Material and Methods – Narrative literature review combined with technical exposition of HFU devices (20–100 MHz mechanical and broadband linear probes). The authors summarise depth–resolution trade-offs, standard scanning protocols and representative clinical images to illustrate HFU performance across anatomical sites and skin conditions. Findings – HFU resolves skin strata down to 10 μm, quantifies tumour thickness (Breslow depth) pre-operatively, delineates BCC margins, detects subepidermal low-echogenic band as a marker of photoageing or atopic dermatitis severity, and guides real-time assessment of fillers, vascular flow, oedema and fibrosis. Frequencies of 20–30 MHz visualise full dermis, 50 MHz epidermis/upper dermis, while lower (7–12 MHz) probes image deeper lesions and lymph nodes.